Characterization of the fine specificity of Bovine CD8 T-Cell responses to defined antigens from the protozoan parasite Theileria parva - Graham, S.P.; Pelle, Roger; Yamage, M.; Mwangi, David Miano; Honda, Y.; Mwakubambanya, R.S.; Villiers, Etienne P. de; Abuya, E.; Awino, Elias; Gachanja, J.; Mbwika, F.; Muthiani, A.M.; et al. (American Society for Microbiology, 2008)
Immunity against the bovine intracellular protozoan parasite Theileria parva has been shown to be mediated by CD8 T cells. Six antigens targeted by CD8 T cells from T. parva-immune cattle of different major histocompatibility complex (MHC) genotypes have been identified, raising the prospect of developing a subunit vaccine. To facilitate further dissection of the specificity of protective CD8 T-cell responses and to assist in the assessment of responses to vaccination, we set out to identify the epitopes recognized in these T. parva antigens and their MHC restriction elements. Nine epitopes in six T. parva antigens, together with their respective MHC restriction elements, were successfully identified. Five of the cytotoxic-T-lymphocyte epitopes were found to be restricted by products of previously described alleles, and four were restricted by four novel restriction elements. Analyses of CD8 T-cell responses to five of the epitopes in groups of cattle carrying the defined restriction elements and immunized with live parasites demonstrated that, with one exception, the epitopes were consistently recognized by animals of the respective genotypes. The analysis of responses was extended to animals immunized with multiple antigens delivered in separate vaccine constructs. Specific CD8 T-cell responses were detected in 19 of 24 immunized cattle. All responder cattle mounted responses specific for antigens for which they carried an identified restriction element. By contrast, only 8 of 19 responder cattle displayed a response to antigens for which they did not carry an identified restriction element. These data demonstrate that the identified antigens are inherently dominant in animals with the corresponding MHC genotypes.